Topography and histomorphology of pineal gland in young goat - KUMAR, PAWAN; KUMAR, SURAJ; SINGH, YASHWANT (The Indian Journal of Animal Sciences, 2013)
The oblong pineal gland of young male goats lacked characteristic pineal stalk except its limb like dorsal and ventral attachments with habenular and posterior commissures. The thin capsuletrabeculae divided the parenchyma into small lobules. The pjnealocytes arranged in different pattems were identifiable into light and dark forms with the predominance of the former. Similarly. 4 types of glial cells were distinguished on the basis of their nuclear morphology. Nerve fibres were irregularly distributed and their density increased towards the pineal I imns. Mast cells were present in small number and corpora arenacea was not observed.